2015
DOI: 10.1007/s00125-015-3598-4
|View full text |Cite
|
Sign up to set email alerts
|

Human islet function following 20 years of cryogenic biobanking

Abstract: Aims/hypothesisThere are potential advantages to the low-temperature (−196°C) banking of isolated islets, including the maintenance of viable islets for future research. We therefore assessed the in vitro and in vivo function of islets cryopreserved for nearly 20 years.MethodsHuman islets were cryopreserved from 1991 to 2001 and thawed between 2012 and 2014. These were characterised by immunostaining, patch-clamp electrophysiology, insulin secretion, transcriptome analysis and transplantation into a streptozot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Tissue. Pancreatic islets and pancreas sections were obtained from human cadaveric donors by the Nordic Network for Clinical Islet Transplantation Uppsala 64 (ethical approval by Uppsala Regional Ethics Board) or the ADI Isletcore at the University of Alberta 65 (ethical approval by Alberta Human Research Ethics Board, Pro00001754), with written donor and family consent for use in research. Work with human tissue complied with all relevant ethical regulations for use of human tissue in research and the study was approved by the Uppsala Regional Ethics Board (2006/348).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue. Pancreatic islets and pancreas sections were obtained from human cadaveric donors by the Nordic Network for Clinical Islet Transplantation Uppsala 64 (ethical approval by Uppsala Regional Ethics Board) or the ADI Isletcore at the University of Alberta 65 (ethical approval by Alberta Human Research Ethics Board, Pro00001754), with written donor and family consent for use in research. Work with human tissue complied with all relevant ethical regulations for use of human tissue in research and the study was approved by the Uppsala Regional Ethics Board (2006/348).…”
Section: Methodsmentioning
confidence: 99%
“…recurrence of severe hypoglycemias, intractable glucose variability, diabetes-related complications), due to the complexity of cell isolation protocols and islet viability after cryopreservation. Although Manning Fox and colleagues recently showed that human islets cryopreserved for 20 years maintained correct purity, functional intracellular Ca 2+ influx and glucose-stimulated insulin secretion (GSIS), these stored cells had decreased levels of insulin content and lower abilities to reverse diabetes in a mouse model as compared with fresh islets [Manning Fox et al 2015].…”
Section: Pancreas and Islet Transplantationmentioning
confidence: 99%
“…Interestingly, there is a relationship between abnormal imprinting genes and growth and development of various diseases. Recent studies show that there is a certain correlation between Kcnq1 gene changes and type 2 diabetes [14], and it is speculated that it is possible that Kcnq1 gene encodes the voltage-gated potassium ion channels and insulin secretion of islet-like cells [2].…”
Section: Discussionmentioning
confidence: 99%